Erratum: Laser-Induced Graphite Plasma Kinetic Spectroscopy under Different Ambient Pressures [Chin. Phys. Lett. Vol. 32, No. 4, 043201(2015)]. (June 2015) - Chaudhary, K.; Rosalan, S.; Aziz, M. S.; Bahadoran, M.; Ali, J; Yupapin, P. P.; Bidin, N.; Saktioto,
Abstract : There is a typewriting mistake in our previous report [Chin. Phys. Lett. 32, 4 (2015) 043201 ], the name of the fourth author M. Bohadoran should be M. Bahadoran. We note that this mistake does not affect the conclusion of our report, and apologize for any inconvenience for readers caused by our oversight.